A common intronic variant in the gene underlying a rare monogenic form of coronary artery disease is associated with low-density lipoprotein cholesterol. (22nd September 2015) - Tomaszewski, M; Charchar, FJ; Barnes, T; Nasmith, WE; Grzeszczak, W; Zukowska-Szczechowska, E; Samani, NJ
Abstract : A rare missense mutation in low-density lipoprotein (LDL) receptor-related protein 6 gene ( LRP6 ) has recently been identified as the primary molecular defect underlying a monogenic form of coronary artery disease (CAD). We hypothesised that common variants in LRP6 could also predispose subjects to elevated LDL-cholesterol. 12 common (minor allele frequency 0.1) tagging single nucleotide polymorphisms (SNP) representative of 96% common genetic variants in LRP6 were genotyped in 212 families with clustering of hypertension and CAD (Silesian Cardiovascular Study, 703 subjects) and in 435 biologically unrelated individuals with clustering of cardiovascular disease (Silesian replication panel). For the purpose of this analysis, subjects were classified as affected if they were on pharmacological lipid-lowering medication or if their fasting LDL-cholesterol was equal to or greater than the lower ATPIII threshold of borderline-high elevation (3.37 mmol/l in subjects aged >19 years, age, gender-specific thresholds for adolescents). Family-based analysis revealed that the minor allele of one of LRP6 SNP (rs10845493) was transmitted from parents to offspring with elevated LDL-cholesterol more frequently than expected by chance (p = 0.005), even after applying a correction for multiple testing. In the independent case–control replication analysis the minor variant of rs10845493 was also associated with an increased risk of elevated LDL-cholesterol (p = 0.0344 after adjustment for age, sex and body mass index (BMI) and controlling for false positive discovery by adaptive permutations). Additional quantitative analysis in 1157 young subjects free of lipid-lowering medication (Young Men's Cardiovascular Association (YMCA) cohort) confirmed a modest effect of LRP6 on circulating concentrations on LDL-cholesterol; each extra minor allele copy of rs10845493 was associated with a 0.09 mmol/l increase in LDL-cholesterol (β = 0.09, SE 0.05, p = 0.0473, after adjustment for age and BMI). The LRP6 genotype was also associated with a surrogate of pro-atherogenic B-phenotype of LDL-cholesterol particles (ratio of triglycerides/high-density lipoprotein cholesterol ⩾1.65); each minor allele copy of rs10845493 increased the risk of LDL-cholesterol B-phenotype in the YMCA cohort by approximately 1.5 (p = 0.0095, after adjustment for age and BMI). These data suggest that a common variant in LRP6 impacts on the risk of LDL-cholesterol elevation and may also contribute to the risk of CAD.